2016
DOI: 10.22456/1679-9216.81167
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Bovine Viral Diarrhea Virus Infection in Wild Boars

Abstract: Background: The farming of wild boars has growing due to the interest of the human consumption of this exotic meat. Such a development may pose an increased risk of disease transmission between boars and domestic animals. The wild boar population has increased in South America in the last years due the absence of predator causing economic losses due to direct damage to crops and risk of disease transmission. The genus Pestivirus within the family Flaviviridae are composed by four recognized species by the Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Phylogenetic analyses based on the whole genome, 5 ′ UTR, and N pro sequences showed that strain was closely related to previously characterized BVDV-1i (JQ920104.1, JQ920215.1, and FJ493484.1) from the UK (90.5% highest nt identity at 5 ′ UTR) and Uruguay (KT833795.1) (90.6 high identity at N pro ). Mósena et al (2017aMósena et al ( , 2017b performed the full genomic sequencing and antigenic characterization of two previously described Brazilian HoBiPeV isolates (Bianchi et al, 2011;Weber et al, 2016aWeber et al, , 2016b. According to the authors, the presented data provided evidence that HoBiPeVs are members of the genus Pestivirus and should be formally recognized as a novel species.…”
Section: Complete Genome Sequencingmentioning
confidence: 94%
See 2 more Smart Citations
“…Phylogenetic analyses based on the whole genome, 5 ′ UTR, and N pro sequences showed that strain was closely related to previously characterized BVDV-1i (JQ920104.1, JQ920215.1, and FJ493484.1) from the UK (90.5% highest nt identity at 5 ′ UTR) and Uruguay (KT833795.1) (90.6 high identity at N pro ). Mósena et al (2017aMósena et al ( , 2017b performed the full genomic sequencing and antigenic characterization of two previously described Brazilian HoBiPeV isolates (Bianchi et al, 2011;Weber et al, 2016aWeber et al, , 2016b. According to the authors, the presented data provided evidence that HoBiPeVs are members of the genus Pestivirus and should be formally recognized as a novel species.…”
Section: Complete Genome Sequencingmentioning
confidence: 94%
“…Recently, this group of viruses has been recognized as a new pestivirus species, named Pestivirus H (ICTV, 2017) (proposed abbreviation, HoBiPeV). The origin, distribution, and relevance of HoBiPeV are still unclear, yet a number of studies demonstrated that these viruses are endemic in Brazil (Cortez et al, 2006;Weber et al, 2016aWeber et al, , 2016bSilveira et al, 2017Silveira et al, , 2018Monteiro et al, 2018aMonteiro et al, , 2018b.…”
Section: A New Player Comes Into Playmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection caused by BVDV in pigs has been reported in China [ 9 ], the Netherlands [ 10 ], Brazil [ 11 , 12 , 13 ], Austria [ 14 ], Germany [ 15 ], Norway [ 16 ], Ireland [ 17 ], Denmark [ 18 ] and others. These data were found not only in domestic pigs but also in wild boars [ 19 ], which raise concerns about risk factors involved in BVDV infection, the clinical form of the disease, and the existence of accurate diagnostic tests. In Brazil, BVDV-1d was frequently reported in cattle [ 20 ].…”
Section: Updates On Bvdv Infection In Swinementioning
confidence: 99%
“…Researchers have adapted numerous variations of PCR methods for the detection of infectious agents, using DNA templates as well as RNA templates after an RT step [ 42 ], which has enabled more accurate, sensible and specific diagnostics. Direct sequencing of the RT-PCR product for fragments of 5′UTR and N-terminal autoprotease (N pro ) may also provide accurate differential diagnosis [ 19 ].…”
Section: Updates On Bvdv Infection In Swinementioning
confidence: 99%